Studi Analisis Echo Train Length dalam K-Space Serta Pengaruhnya Terhadap Kualitas Citra Pembobotan T2 FSE pada MRI 1.5 T - Simanjuntak, Josepa ND; Nur, Muhammad; Hidayanto, Eko (BERKALA FISIKA, 2014)
The influence of echo train length (ETL) toward image quality of sagital lumbal on MRI using T2-weighted FSE was analyzed on 20 images from four patients. Quantitative data analysis was performed using ROI two methods: image processing method on MRI’s computer and using matlab software, then conducted the statistical test. The result of SNR from these two methods obtained the highest value of SNR at CSF tissue and the highest value of CNR at CSF-corpus tissue and CSF-medulla spinalis with ETL=16. From statistical test of SNR result directly from MRI’s computer image was obtained the significant value at corpus tissue = 0.603, CSF = 0.082, and Fat = 0.213 (P > 0,05), discus = 0.022, Medulla Spinalis (MS) = 0.010 (P < 0.05), and for CNR result of CSF-corpus tissue has significant value = 0,023, corpus-MS = 0.011 (P < 0.05). By using matlab programming method obtained significant SNR result at corpus tissue = 0.000, CSF = 0,000, Fat = 0,000, discus = 0,000, Medulla spinalis = 0,000 (P < 0,05), and for the CNR result of Dicus-corpus tissue has significant value = 0.044, Dicus-MS= 0.045 (P , 0.05). These results pointed out that ETL and T2 weighted influence the Image quality of MRI, which are the image contrast at FSE and software ability of matlab to analyze the image quality of MRI. SNR and contrast are important aspect in the process of image optimization, the higher SNR value provide the better image in giving diagnose information. Keywords : MRI, Echo train length (ETL), K-space, Fast spin echo, Contras to noise ratio, Signal to noise ratio.